2009
DOI: 10.1016/j.psychres.2008.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Are self-injurers impulsive?: Results from two behavioral laboratory studies

Abstract: Common clinical wisdom suggests that people who engage in self-injury are impulsive. However, virtually all prior work in this area has relied on individuals' self-report of impulsiveness, despite evidence that people are limited in their ability to accurately report on cognitive processes that occur outside awareness. To address this knowledge gap, we used performance-based measures of several dimensions of impulsiveness to assess whether people engaging in non-suicidal self-injury (NSSI) demonstrate greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
128
5
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(154 citation statements)
references
References 49 publications
13
128
5
8
Order By: Relevance
“…We can see from the findings reported that the evaluation of decision making skills in children and adolescents, besides useful in the clinical characterization of different psychopathologies, has also a potential use as an indicator of function and social adaptation within each disorder 17,27,46,47,48,51, 54 . Additional investigations about this relationship in children and adolescents with psychiatric disorders are needed.…”
Section: Sample Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We can see from the findings reported that the evaluation of decision making skills in children and adolescents, besides useful in the clinical characterization of different psychopathologies, has also a potential use as an indicator of function and social adaptation within each disorder 17,27,46,47,48,51, 54 . Additional investigations about this relationship in children and adolescents with psychiatric disorders are needed.…”
Section: Sample Resultsmentioning
confidence: 99%
“…Among the studies reviewed, only eleven used the Iowa Gambling Task to assess decision-making 11,20,21,26,29,[47][48][49]51,52,54 . Seven of them used variations very similar to the original task in which there were small changes in the amount of the loan, gains and punishments after the choices 17,28,31,32,36,40,44 .…”
Section: Amongmentioning
confidence: 99%
“…A literatura aponta estudos que avaliam funções executivas (Ohmann et al, 2008;Oldershaw et al, 2009;Janis;Fikke et al, 2010), …”
Section: Inventory (Psi)unclassified
“…NSSI is often performed only a few minutes after the urge to engage in NSSI has arisen (Favazza & Conterio, 1989;Klonsky & Olino, 2008;, and self-reported impulsivity has shown to be associated with NSSI (Herpertz, Sass, & Favazza, 1997;Janis & Nock, 2009;You & Leung, 2012). There has however also been some inconsistency in results, depending among other things on how impulsivity is conceptualized (Glenn & Klonsky, 2010a;Janis & Nock, 2009). Glenn and Klonsky (2010a) found that it was mainly urgency, defined as "a tendency to engage in rash behaviors in the face of negative affect" (p. 72), that differed between groups.…”
Section: Psychiatric Disorders and Symptomatologymentioning
confidence: 99%